Optimal Target Channel Sequence Design for Multiple Spectrum Handoffs in Cognitive Radio Networks - Wang, Li-Chun; Wang, Chung-Wei; Chang, Chung-Ju (My University, 2012)
In this paper, we investigate how to determine an optimal target channel sequence with the minimum cumulative handoff delay in cognitive radio networks. When the secondary user encounters multiple spectrum handoffs during its transmission period, the effects of multiple interruptions from the high-priority primary users and the traffic statistics of both the primary and the secondary users should be incorporated in the design of the optimal target sequence. The optimal target channel sequence can guild the secondary user to change its operating channel when the primary user's interruptions occur. With M candidate channels and L elements in the target channel sequence for spectrum handoffs, the exhaustive search (ES) requires time complexity of O(M-L). In this paper, we propose a dynamic programming (DP) algorithm with time complexity of O(LM2) to determine an optimal target channel sequence. Furthermore, we propose a greedy algorithm with time complexity of O(M) and prove that the greedy algorithm only requires comparing six target channel sequences. Numerical results show that the low-complexity greedy algorithm can yield similar cumulative handoff delay performance as the optimal DP-based or ES-based algorithms in most cases except when the primary users' service time distributions at their operating channels are different.
Keywords: Cognitive radio; spectrum handoff; spectrum obility; preemptive priority; queueing theory